Maternal Transmission of Rotavirus to Calves and Comparison of Colostrum and Fecal Microbiota in Holstein and Hanwoo Cattle - Seon-Ho Kim; Michelle Miguel; Ye Pyae Naing; Yong-Il Cho; Sang-Suk Lee (Veterinary Sciences)
This study aimed to evaluate rotavirus transmission to calves and analyze microbial communities in cow milk and neonatal calf feces within dairy and beef cattle. A total of 20 cattle, Hanwoo (n = 10), and Holstein (n = 10) were allotted for the study, with each breed comprising five cows and five calves. Colostrum samples were obtained from the dam, while feces were obtained from both the dam and calf. Group A rotavirus was identified in the fecal samples through real-time reverse transcription PCR (RT-qPCR). Bacterial communities present in the colostrum and bovine feces were explored using 16S rRNA metagenomic sequencing. The RT-qPCR results showed that the Cq value of one calf and one cow in the Holstein group was < 35, confirming the presence of rotavirus, whereas the Cq value in the Hanwoo group was > 35, indicating a negative result. For the bacterial communities, significant differences (p < 0.05) were found between the colostrum and fecal samples from the dams and calves, but there were no significant differences between Hanwoo and Holstein cattle. Alpha diversity analysis showed that the Chao1 and Shannon indices revealed significant differences (p < 0.05) among the sample types (cow colostrum, cow feces, and calf feces). The bacterial communities in various sample types from both Hanwoo and Holstein cattle were dominated by the phyla Firmicutes, Proteobacteria, and Bacteroidetes. In addition, the genera shared between the cow colostrum and calf fecal microbiota were higher than those shared between cow and calf feces. Overall, the current study detected rotavirus in Holstein but not in Hanwoo cattle; however, no clear evidence showed the transmission of rotavirus from dam to calf. Moreover, significant variations in bacterial compositions were observed among calf feces, cow feces, and colostrum samples, suggesting the presence of unique microbial profiles.